Complementary Buck-Boost Converter with Variable Voltage Tracking System for Photovoltaic Applications - Khader, Sameer (European Journal of Scientific Research , EJSR, 2012)
This paper proposed solutions for enhancing the behaviors of photovoltaic generation module (PV Array) with and without using buck-boost converter for realizing constant output voltage according to reference voltage at constant and variable solar irradiation. The proposed solutions describe single and double buck-boost (complementary) dc chopper with presence of various control strategies/modules such as pulse width modulation, maximum power point tracking strategy (MPPT) and variable voltage tracking strategy (VVT). The obtained results according to proposed models state that complementary chopper realized better performances in case of VVT strategy rather than MPPT control strategy when direct grid connection is required as major criteria for constant output voltage. As first stage Matlab/ Simulink is used to simulate the proposed models, where the obtained analytical and simulation results are going to be experimentally verified in the second stage of this work.
Keywords: Photovoltaic systems, DC Choppers, Smart Grids, PWM, Soft Switching.